The historical social cost of fossil and industrial CO₂ emissions - Wilfried Rickels; Felix Meier; Martin Quaas (Nature Climate Change, 2023)
Past CO 2 emissions have been causing social costs and continue to reduce wealth in the future. Countries differ considerably in their amounts and time profiles of past CO 2 emissions. Here we calibrate an integrated assessment model on past economic and climate development to estimate the historical time series of social costs of carbon and to assess how much individual countries have reduced global wealth by their fossil and industrial-process CO 2 emissions from 1950 to 2018. Historical social costs of carbon quantify the long-lasting wealth reduction by past CO 2 emissions, which we term `climate wealth borrowing', as economic output has been generated at the expense of future climate damages. We find that the United States and China have been responsible for the largest shares of global climate wealth borrowing since 1950, while the per-capita pattern is quite different.
Keywords: 330